2017
DOI: 10.1007/s00467-017-3711-7
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid cells: current progress and emerging challenges in renal regeneration

Abstract: Amniotic fluid (AF) contains a heterogeneous population of cells that have been identified to possess pluripotent and progenitor-like characteristics. These cells have been applied in various regenerative medicine applications ranging from in vitro cell differentiation to tissue engineering to cellular therapies for different organs including the heart, the liver, the lung, and the kidneys. In this review, we examine the different methodologies used for the derivation of amniotic fluid stem cells and renal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…Stem cells have different capacities for integrating into target organs, as we showed with AFSC . We found almost no integration in a CKD model (after 5 days) and very low integration in ATN models despite a positive therapeutic signal.…”
Section: Important Variables In the Preclinical Renal Regeneration LIsupporting
confidence: 51%
See 3 more Smart Citations
“…Stem cells have different capacities for integrating into target organs, as we showed with AFSC . We found almost no integration in a CKD model (after 5 days) and very low integration in ATN models despite a positive therapeutic signal.…”
Section: Important Variables In the Preclinical Renal Regeneration LIsupporting
confidence: 51%
“…We demonstrated that stem cells derived from amniotic fluid are renoprotective in animal models of glycerol-induced AKI, as well as CKD [4,37]. AFSC seem to protect tubular and glomerular cells by stimulating endogenous repair mechanisms, thus reducing inflammation and fibrosis [38].…”
Section: Different Types Of Stem Cells and Preclinical Models Of Renamentioning
confidence: 89%
See 2 more Smart Citations
“…Several studies have recently shown that MSCs play an important role in preserving renal microvessels and relieving kidney injury in a variety of kidney disease models (Table 3 ). Furthermore, MSCs can be obtained from a variety of tissues, including adipose tissue [ 101 , 102 ], bone marrow [ 103 105 ] and amniotic fluid [ 106 , 107 ], and have been reported to have antioxidative, anti-inflammation, proangiogenic, and immunomodulatory function in numerous experimental studies. More specifically, the functions (including differentiation, immunosuppression, and release of cytokines and factors) of MSCs isolated from adipose tissue of renal disease patients were not affected by exposure to uremic conditions.…”
Section: Therapeutic Strategies Targeting Injured Microvesselsmentioning
confidence: 99%